Efficacy of Electronic Acupuncture Shoes for Chronic Low Back Pain: Double-Blinded Randomized Controlled Trial - Yeh, Bo-Yan; Liu, Geng-Hao; Lee, Tzung-Yan; Wong, Alice May-Kuen; Chang, Hen-Hong; Chen, Yu-Sheng (JMIR Publications, 2020)
BackgroundChronic low back pain is a common problem and is associated with high costs, including those related to health care and indirect costs due to absence at work or reduced productivity. Previous studies have demonstrated that acupuncture or electroacupuncture can relieve low back pain. Electronic acupuncture shoes (EAS) are a novel device designed in this study. This device combines the properties of acupuncture and transcutaneous electrical nerve stimulation for clinical use. ObjectiveThe aim of this study was to evaluate the efficacy of EAS in patients with chronic low back pain. MethodsIn this prospective double-blinded randomized controlled study, the data of 83 patients who experienced chronic low back pain were analyzed. Patients came to our clinic for 20 visits and underwent assessment and treatment. Patients were randomly allocated to receive either EAS plus placebo nonsteroidal anti-inflammatory drugs (NSAIDs) (EAS group, n=42) or sham EAS plus NSAIDs (NSAID group, n=41). The visual analog scale (VAS) score and range of motion were assessed at baseline, before and after each EAS treatment, and 2 weeks after the last treatment. The time for achieving pain remission was recorded. Quality of life was assessed at the 2nd, 14th, and 20th visits. ResultsAfter 6 weeks of treatment, the treatment success rate in each visit in the EAS group was higher than that in the NSAID group, as revealed by the intention-to-treat (ITT) and per-protocol (PP) analyses, but significant differences were observed only during the 16th visit in the ITT analysis (EAS group: 31/37, 84% and NSAID group: 21/34, 62%; P=.04). The change in the VAS score from baseline in each visit in the EAS group was greater than that in the NSAID group, as revealed by the ITT and PP analyses, and significant differences were observed in the 5th visit and 9th visit in the ITT analysis (P=.048 and P=.048, respectively). Significant differences were observed in the left rotation in the 2nd visit and 4th visit (P=.049 and P=.03, respectively). No significant differences were observed in the VAS score before and after treatment in each visit and in the quality of life in both groups. ConclusionsEAS might serve as a reliable alternative therapeutic tool for patients with chronic low back pain who are contraindicated for oral NSAIDs. Trial RegistrationClinicalTrials.gov NCT02468297 https://clinicaltrials.gov/ct2/show/NCT02468297